From book to e-book: A digital revolution in French cultural studies?. (August 2014) - Duché, Véronique; Bourgeois, Bertrand
The rise of the digital revolution does not only relate to science and business, but also to literature and the arts. Therefore it is a topic worth considering for French cultural studies. This article aims to show how profoundly e-technology has changed the way French readers interact with books and all forms of textual production – reading, consuming, learning, selecting, sharing, etc. – despite the institutional resistance of a so-called 'French conservative' approach towards books and culture. As a matter of fact, more and more artists and writers are using e-technology. We will demonstrate, via two case studies of livres d'artiste by Serge Bouchardon and Nicolas Frespech, how these e-books can be seen as perfect cultural studies 'objects', since they combine different media and exemplify some of the striking shifts in the French cultural field.